FIXED-BED REACTOR MODELS AND SO₂ ADSORPTION - Sato, Gabriel Augusto Lopes; Chavarette, Fábio Roberto; Faria, Henrique Antonio Mendonça (Editora Impacto Científico, 2025)
This chapter addresses introductory concepts regarding the mathematical modeling of sulfur dioxide adsorption in a fixed-bed reactor column utilizing chitosan as the bio adsorbent matrix. The study is situated within the field of process engineering and emphasizes the importance of dynamic models, based on Partial Differential Equations (PDEs), for predicting the behavior of real and complex systems, such as distributed ones. The objective was to present the two coupled PDEs that describe the mass balance of the gas, one for the gaseous phase along the bed and the other for diffusion within the solid phase. The selection of this biopolymer represents a sustainable innovation, leveraging its affinity for polluting gases. The numerical resolution of these PDEs, aided by software such as Matlab and Origin, allows for the prediction of the process dynamics and the analysis of the effects of variations in operational and structural parameters of the column and the matrix. The theoretical aspects presented provide an understanding of the model for the removal of atmospheric pollutants, establishing a foundation for future experimental research and the optimization of the pollution control process.DOI: https://doi.org/10.56238/edimpacto2025.065-002